Narrative review of factors associated with SARS-CoV-2 coinfection in Middle Eastern countries and the need to vaccinate against preventable diseases - Majid Alshamrani; Fayssal Farahat; Ali Albarrak; Aiman El-Saed; Atef M. Shibl; Ziad A. Memish; Mostafa Mousa; Hammam Haridy; Abdulhakeem Althaqafi (Journal of Infection and Public Health)
This review evaluated the frequency of, and outcomes associated with, bacterial, fungal, and viral coinfection with SARS-CoV-2 in Middle Eastern countries via a PubMed search through February 2023. Ninety articles reported bacterial (n = 57), fungal (n = 32), and viral (n = 32) coinfections. High frequencies of coinfection with COVID-19 were identified, with rates and outcomes varying by setting, pathogen, surveillance/detection method, population characteristics, and drug-resistance status. Mortality rates were higher in patients with community-acquired (10.0 −42.9 %) and hospital-acquired (51.5 −66 %) bacterial coinfection versus those without (10.5 −21.7 %). Outcomes were worse with than without fungal coinfection, and fatality rates with mucormycosis coinfection reached 66.7 %. Outcomes with viral coinfection were highly variable; however, some data suggested a positive corelation between COVID-19 severity and influenza A and adenovirus coinfection. The negative outcomes associated with bacterial, fungal and some viral coinfections in individuals with COVID-19 support regular vaccination against vaccine-preventable diseases caused by these pathogens, especially among at-risk populations.